'A Passion for Passionlessness': The Cappadocian Fathers and Iris Murdoch on Apatheia as a Spiritual Ideal. (10th February 2017) - Guise, Margaret
Abstract: As the centenary of the birth of Iris Murdoch approaches, reappraisals of her literary work, which continues to divide critical opinion, seem due. This article posits that rereading her novels in rapprochement with the writings of the group of fourth-century theologians known as the 'Cappadocian Fathers' reveals a 'passion for passionlessness' within the Murdochian corpus which has hitherto been little explored, and affords the possibility of a soteriological 'embrace' between these very discrete conversation partners.